POTENSI SENTRA INDUSTRI HALAL KOPI DI DESA JATIARJO DALAM PERSPEKTIF MAQASHID SYARIAH - Rosa, Amelia; Khayati, Ismatul (Politeknik Bisnis Indonesia, 2024)
The halal industry is an economic sector related to the provision of products and services based on halal principles in Islam. Jatiarjo Village is known as one of the coffee producers. This study aims to explore the potential of the halal industry in Jatiarjo Village through coffee commodities, which is expected to increase the income and welfare of the local community. This research is a qualitative study using primary data obtained through field observations and in-depth interviews with selected informants. The results showed that the people of Jatiarjo Village, especially coffee business actors, felt that the potential of the halal industry from coffee commodities was very large in increasing their employment opportunities, income and welfare.